Influence of Leishmania (Viannia) braziliensis infection on the attractiveness of BALB/c mice to Nyssomyia neivai (Diptera: Psychodidae) - da Rocha Silva, Flávia Benini [UNESP]; Miguel, Danilo Ciccone; Machado, Vicente Estevam [UNESP]; Oliveira, Wanderson Henrique Cruz [UNESP]; Goulart, Thais Marchi; Tosta, Christiann Davis; Pinheiro, Hildete Prisco; Pinto, Mara Cristina [UNESP] (Public Library of Science (PLoS), 2019)
Background Phlebotomine sand flies are vectors for several pathogens, with Leishmania being the most important. In Brazil, the main aetiological agent of American cutaneous leishmaniasis (ACL) is Leishmania (Viannia) braziliensis, and Nyssomyia neivai is one of its main vectors in São Paulo state and other areas of South America. Similar to other haematophagous insects, sand flies use volatile compounds called kairomones to locate their hosts for blood meals. A possible increase in the attractiveness of hosts infected with Leishmania infantum to their vectors has been demonstrated. In the present study, we aimed to investigate whether L. braziliensis-infected hosts present higher attractiveness to Ny. neivai and to identify differences in the volatile compounds released by infected and uninfected mice. Results Behavioural experiments in which sand fly females directly fed on infected or uninfected mice showed no significant differences in the attractiveness of the mice or the blood volume ingested. Y-tube olfactometer bioassays also revealed no significant differences in the attractiveness of these hosts to Ny. neivai. No differences were observed in the profiles of the volatile compounds released by the two groups of mice. However, PCA and cluster analysis were able to classify the 31 identified compounds into three clusters according to their abundances. This classification showed a possible role for individual variation in the absence of differences in volatile profiles and attractiveness between infected and uninfected mice. Conclusion In this first cross-sectional study with an aetiological agent of ACL, there were no statistically significant differences in the attractiveness of infected hosts to their vector.